1986
DOI: 10.1203/00006450-198607000-00001
|View full text |Cite
|
Sign up to set email alerts
|

31P Nuclear Magnetic Resonance Study of the Effect of Hypoxemia on Neonatal Status Epilepticus

Abstract: METH ODSbolic perturbat ion imp osed by hypoxia, by seizures during normoxia, and by seizures during hypoxia. The se are topi cs of major clinical relevance since seizures in the neon ate are frequ entl y manifested by apnea and cyanosis (2).In measuring cerebral metabolic state , we employed high resolution 31P_NMRspectroscopy, a powerful technique for noninvasi ve, sequential measurement of brain energy change s in vivo (6-9). These in vivo measur ements were corro borated by in vitro determ inati on of brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 21 publications
(35 reference statements)
1
7
0
Order By: Relevance
“…These animals were randomized and subjected to the same experimental conditions. CBF was measured at the end of the 45-minute period of experimental observation according to the method of Sakurada and associates [ 20,24,261. The electroencephalogram (EEG) was continuously monitored while the animal was in the spectrometer with scalp electrodes, a Grass Model 6 polygraphic recorder, and low-pass radiofrequency filters.…”
Section: Methodsmentioning
confidence: 99%
“…These animals were randomized and subjected to the same experimental conditions. CBF was measured at the end of the 45-minute period of experimental observation according to the method of Sakurada and associates [ 20,24,261. The electroencephalogram (EEG) was continuously monitored while the animal was in the spectrometer with scalp electrodes, a Grass Model 6 polygraphic recorder, and low-pass radiofrequency filters.…”
Section: Methodsmentioning
confidence: 99%
“…They also reported that rat pups were able to maintain almost constant their reserves in cerebral high‐energy phosphate. In a more recent series of experiments using phosphorous nuclear magnetic resonance spectroscopy (31‐P NMRS), Young et al (1985a, 1985b) examined the cerebral metabolism during bicuculline‐induced SE in various newborn animals, paralyzed and ventilated during SE. They showed that the energy balance in these brains was well preserved, even during prolonged convulsions.…”
Section: What Has Been Learned From the Laboratorymentioning
confidence: 99%
“…Twenty-five animals were used in the CBF studies (Table 1); 37 animals were used in the metabolism studies (control nine; hypotension six; seizure 10, seizure-hypotension 12). Values from six of the 10 seizure animals have been previously reported (9). RESULTS Arterial blood pressure was transiently increased in animals in the seizure group (Fig.…”
Section: Methodsmentioning
confidence: 85%
“…The method has been previously described in detail (8,9). Briefly, mongrel dogs (1-10 days old) were anesthetized for 5 min with halothane while undergoing tracheostomy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation